Biohydrogen production from food waste by coupling semi-continuous dark-photofermentation and residue post-treatment to anaerobic digestion: A synergy for energy recovery. (14th December 2015) - Ghimire, Anish; Valentino, Serena; Frunzo, Luigi; Trably, Eric; Escudié, Renaud; Pirozzi, Francesco; Lens, Piet N.L.; Esposito, Giovanni
Abstract: This study aimed at maximizing the energy yields from food waste in a three-step conversion scheme coupling dark fermentation (DF), photofermentation (PF) and anaerobic digestion (AD). Continuous H2 production was investigated over a period of nearly 200 days in a thermophilic semi-continuous DF process with no pH control. The highest H2 yield of 121.45 ± 44.55 N L H2 /kg VS was obtained at an organic loading rate of 2.5 kg VS/m 3 /d and a hydraulic retention time of 4 days. The DF effluents mainly contained volatile fatty acids (VFAs) and alcohols as metabolites and un-hydrolyzed solid residues. The supernatant, after separation, was used to recover H2 in a PF using Rhodobacter sphaeroides . The solid residual fraction along with PF effluent was converted into methane by anaerobic digestion. By combining DF and PF, the H2 yield from the food waste increased 1.75 fold. Moreover, by adding AD as a post treatment of the DF residue, the total energy yield was substantially increased to reach 5.55 MJ/kg VSfood waste added, versus 3.55 MJ/kg VSfood waste when applying solely AD. Highlights: Three step conversion of food waste to biohydrogen and methane is presented. Coupling of dark and photo fermentation (DF-PF) can increase biohydrogen yields. Anaerobic digestion (AD) can valorize DF-PF residues by conversion to methane. High energy yields and treatment of waste can be achieved by integrated DF-PF-AD.